Hyponatraemia Induced by Terlipressin in Patients Diagnosed with Decompensated Liver Cirrhosis and Acute Variceal Bleeding - Mahmoud Elshehawy; Richel Merin Panicker; Alaa Amr Abdelgawad; Patrick Anthony Ball; Hana Morrissey (Medicines)
Background: Hyponatraemia is a rare but potentially life-threatening complication of terlipressin therapy. Case history: In the current case, a 39-year-old female with decompensated liver cirrhosis (Child-Pugh C) and acute variceal bleeding experienced a precipitous decline in serum sodium—from 136 mmol/L to 115 mmol/L—within 48 h of initiating terlipressin therapy. This was accompanied by marked fluid retention, reduced urine output, and symptoms of confusion and agitation. Laboratory tests confirmed dilutional hyponatraemia, characterized by urinary sodium <20 mmol/L and urine osmolality <100 mOsm/kg, indicating excessive free water reabsorption. Outcomes: The prompt discontinuation of terlipressin, fluid restriction and the cautious administration of hypertonic sodium chloride solution (2.7% NaCl) achieved a gradual normalization of sodium levels and resolution of symptoms. Fluid balance monitoring revealed a marked diuretic response following terlipressin cessation. This case aligns with existing reports, emphasizing the dual vasopressin receptor activity of terlipressin and its capacity to induce hyponatraemia, particularly in cirrhotic patients with preserved renal function and higher baseline sodium levels. Conclusions: This case and a literature review underscored the critical need for early fluid balance monitoring to detect retention. This case highlights the importance of individualized risk assessment, multidisciplinary management, and vigilant sodium correction to avoid complications. Practical recommendations are outlined to aid clinicians in the recognition and management of terlipressin-induced hyponatraemia.